Virtual prototyping of adhesively restored, endodontically treated molars. - Magne P (Journal of Prosthetic Dentistry, 2010)
STATEMENT OF PROBLEM: Teeth and dental restorations are difficult to model because of their complex anatomical shape and layered structure. PURPOSE: The purpose of this investigation was to describe the use of an efficient virtual prototyping method for the comparison of bonded porcelain and composite resin onlays to restore endodontically treated molars. MATERIAL AND METHODS: An intact mandibular molar was digitized with a micro-CT scanner. Surface contours of enamel and dentin were fitted following tooth segmentation based on pixel density using an interactive medical image processing software (Mimics). Standard triangle language files of enamel and dentin surfaces were then exported to a design and meshing software (3-matic). The root filling, base material, and a 3.0-mm-thick onlay were created by merging primitive shapes. Surface splitting, removal of unwanted surfaces, and remeshing allowed generation of an assembly with optimized interfacial mesh congruence and T-junctions. Solid 3-dimensional (3-D) models obtained in a finite element software (Marc/Mentat) were subjected to nonlinear contact analysis to simulate occlusal loading at 200 N and 700 N. Maximum principal stress values were used to calculate the risk of fracture and for validation with existing experimental data. RESULTS: There were similar stress distributions at 200 N (maximum peak values of 24 to 26 MPa) for both restorative materials, but marked differences at 700 N, with the porcelain onlay showing occlusal stress peaks more than 30% higher than composite resin. High stress concentrations were found at 700 N at the root level of the porcelain-restored tooth (95 MPa). For the composite resin onlay, secondary peaks of stress at the 700-N load were found above the cemento-enamel junction (47 MPa) with only minor effects at the root. The risk of fracture was increased for porcelain onlays, which correlated with the existing validation data and the decreased risk of fracture below the cemento-enamel junction (CEJ) observed for composite resin onlays. CONCLUSIONS: The virtual prototyping method can generate detailed and valid 3-D finite element models of a restored, endodontically treated molar. The decreased risk of fracture and more favorable stress distribution of adhesive composite resin onlays compared to porcelain onlays were confirmed. This method is efficient and may be used for other medical and dental applications.